2015
DOI: 10.1142/s0218301315500500
|View full text |Cite
|
Sign up to set email alerts
|

New analysis of the low-energy π±p differential cross-sections of the CHAOS Collaboration

Abstract: In a previous paper, we reported the results of a partial-wave analysis (PWA) of the pion–nucleon (πN) differential cross-sections (DCSs) of the CHAOS Collaboration and came to the conclusion that the angular distribution of their π+p data sets is incompatible with the rest of the modern (meson factory) database. The present work, re-addressing this issue, has been instigated by a number of recent improvements in our analysis, namely regarding the inclusion of the theoretical uncertainties when investigating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(87 citation statements)
references
References 21 publications
7
78
2
Order By: Relevance
“…The combination 2a + 1+ + a + 1− has been stable during the last three decades. Our result 2a + 1+ + a + 1− = (199 ± 14) · 10 −3 m −3 π , obtained from (7) using our values for coefficient c 1 , effective range b + 0+ and scattering length a + 0+ , is in good agreement with those obtained in partial wave analyses performed during the last several years [37,38,39], e.g. 2a + 1+ + a + 1− = (203.9 ± 1.9) · 10 −3 m −1 π [39].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The combination 2a + 1+ + a + 1− has been stable during the last three decades. Our result 2a + 1+ + a + 1− = (199 ± 14) · 10 −3 m −3 π , obtained from (7) using our values for coefficient c 1 , effective range b + 0+ and scattering length a + 0+ , is in good agreement with those obtained in partial wave analyses performed during the last several years [37,38,39], e.g. 2a + 1+ + a + 1− = (203.9 ± 1.9) · 10 −3 m −1 π [39].…”
Section: Discussionsupporting
confidence: 90%
“…Our result 2a + 1+ + a + 1− = (199 ± 14) · 10 −3 m −3 π , obtained from (7) using our values for coefficient c 1 , effective range b + 0+ and scattering length a + 0+ , is in good agreement with those obtained in partial wave analyses performed during the last several years [37,38,39], e.g. 2a + 1+ + a + 1− = (203.9 ± 1.9) · 10 −3 m −1 π [39]. In view of the spread among the various isoscalar scattering lengths mentioned above, we performed two tests to study the sensitivity of our determination of σ πN to a variation of the scattering length.…”
Section: Discussionsupporting
confidence: 90%
“…In more detail, the discrepancy could be attributed to about equal parts to the πN coupling constant, a + 0+ , and the dispersive integrals. 14 A similar picture emerged from the subthreshold parameters extracted with dispersive techniques from PWAs in [213][214][215][297][298][299], where the input from the GWU group [296,[300][301][302] consistently produced a larger σ-term than the PWAs from [76][77][78] (see also [303][304][305][306][307] in this context). Similarly, extractions of the σ-term from ChPT [20,308] tend to reproduce the value corresponding to the PWA that is used to determine the LECs in the physical region.…”
Section: Previous Extractionsmentioning
confidence: 89%
“…In a series of subsequent papers, two πN-related issues were mainly addressed: a) the reproduction of the low-energy (T ≤ 100 MeV) π ± p elastic-scattering and charge-exchange π − p → π 0 n (CX) data [4,5,6,7], including the extraction of the values of the low-energy constants (LECs) of the πN system, and b) the violation of isospin invariance in the hadronic part of the πN interaction 1 [4,7,9]. The model was also involved in an iterative procedure which resulted in the determination of the electromagnetic (em) corrections [10,11], i.e., of the corrections which must be applied to the πN phase shifts and to the partialwave amplitudes on the way to the evaluation of the low-energy observables, namely of the differential cross section (DCS) and of the analysing power (AP).…”
Section: Introductionmentioning
confidence: 99%
“…The model was also involved in an iterative procedure which resulted in the determination of the electromagnetic (em) corrections [10,11], i.e., of the corrections which must be applied to the πN phase shifts and to the partialwave amplitudes on the way to the evaluation of the low-energy observables, namely of the differential cross section (DCS) and of the analysing power (AP). The long-term use of this model has demonstrated that it can account for the experimental information available at low energies almost as successfully as simple parameterisations of the K-matrix elements [4,5,6,7,12], which do not contain theoretical constraints other than the expected low-energy behaviour of these elements. One may thus conclude that the model constitutes a firm basis for the parameterisation of the dynamics of the πN system at low energies.…”
Section: Introductionmentioning
confidence: 99%